If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -5y = 20x + -10 Reorder the terms: 15x + -5y = -10 + 20x Solving 15x + -5y = -10 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 15x + -20x + -5y = -10 + 20x + -20x Combine like terms: 15x + -20x = -5x -5x + -5y = -10 + 20x + -20x Combine like terms: 20x + -20x = 0 -5x + -5y = -10 + 0 -5x + -5y = -10 Add '5y' to each side of the equation. -5x + -5y + 5y = -10 + 5y Combine like terms: -5y + 5y = 0 -5x + 0 = -10 + 5y -5x = -10 + 5y Divide each side by '-5'. x = 2 + -1y Simplifying x = 2 + -1y
| 7q-18=3 | | (2x/3)-1 | | 2*2x-3=65 | | x^2-4x+4-49=0 | | 22x-x= | | 2*2x+3-65=0 | | (2+i)-(6-2i)= | | 2x^2+3-65=0 | | 43+x-19=36 | | 80+x-68=32 | | x^2-6x+-49=0 | | -2(4x-2-4)=5(x+2) | | 2n-13=17 | | 72+x-35=49 | | -2(4x-2)=5(x+1) | | 8x+3=7x+6 | | (5-2x)/x=1/4 | | 6b^2-10=14 | | x^2+2c+24=0 | | x+39=7 | | 8sinx-3=0 | | 3x-2-2x=1+2x+8 | | (2x-5)1/2=7 | | 5(3x-2)=2(x+2) | | 2(f-4)+8-4h=-3 | | 3x^2-118x+899=0 | | y=4x(2x+3)+1 | | T-12/6=4/3 | | 11x+6=8x+9 | | X*2x+3-65=0 | | 3(3x+5)=3x-1 | | 2x^2-12x+25=y |